Multiple sclerosis associated with Leber's Hereditary Optic Neuropathy. - Palace, J (2009)
The cause of multiple sclerosis is unknown although it is recognised to involve an inflammatory process associated with demyelinating plaques and more widespread neurodegeneration. It appears to have become progressively more common in females which is further discussed in this issue, and genetic factors, as identified to date, appear to play only a moderate role. One curious observation is that Leber's Hereditary Optic Neuropathy (LHON), a rare genetic syndrome, presents clinically overwhelmingly in males, but can be associated with an MS-like illness and when it does it occurs mainly in females. It is interesting to examine this further to assess if this could give us any clues as to the pathogenesis of MS.